2016
DOI: 10.1103/physrevb.93.081207
|View full text |Cite
|
Sign up to set email alerts
|

Silicon vacancy center in4H-SiC: Electronic structure and spin-photon interfaces

Abstract: Defects in silicon carbide are of intense and increasing interest for quantum-based applications due to this material's properties and technological maturity. We calculate the multi-particle symmetry adapted wave functions of the negatively charged silicon vacancy defect in hexagonal silicon carbide via use of group theory and density functional theory and find the effects of spin-orbit and spinspin interactions on these states. Although we focused on V − Si in 4H-SiC, because of its unique fine structure due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
125
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 47 publications
10
125
0
Order By: Relevance
“…In agreement with previous theoretical estimates [28], these results disprove the existence of an undistorted T d symmetric silicon vacancy [22] in 4H -SiC, which was one of the basic assumptions of model II [14]. Furthermore, both the calculated ZPL energies and the hyperfine values are in good agreement with the experimental data.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with previous theoretical estimates [28], these results disprove the existence of an undistorted T d symmetric silicon vacancy [22] in 4H -SiC, which was one of the basic assumptions of model II [14]. Furthermore, both the calculated ZPL energies and the hyperfine values are in good agreement with the experimental data.…”
supporting
confidence: 80%
“…The multiplet structure of these defects includes a 4 A 2 ground state, low-energy 4 A 2 and 4 E optically allowed excited states, and other spin-1/2 shelving states between the ground and optical excited states [28]. Accordingly, in our first-principles calculations, we consider the 4 A 2 ground state and the lowest-energy optically excited state, either the 4 A 2 or the 4 E state.…”
mentioning
confidence: 99%
“…The most important difference is that in its stable configuration it involves five active electrons (or, equivalently, three holes). Moreover, the distance of the carbon located along the C 3 -symmetry axis from the vacancy, as calculated with DFT [26], is approximately equal to the distances of the basal carbons from the vacancy. As a result, the C 3v symmetry of this defect is in fact very close to T d in the 4H and 6H polytypes [27,26], and is exactly T d in 3C SiC.…”
Section: Silicon Monovacancymentioning
confidence: 97%
“…1(a). It has been suggested that optical excitation leads to spin polarization into the M S ¼ AE1=2 spin sublevels of the ground state due to spin-dependent intersystem crossing [19,32,[46][47][48][49]. The fluorescence emission is brighter when the system is in one of the M S ¼ AE3=2 states which is the basis for optical detection of electron spin resonance [19,46].…”
Section: Electron Spin Resonance Of Silicon Vacancy In Silicon Camentioning
confidence: 99%